Small anthropomorphic figurines in clay at Gipka neolithic settlements - Loze, Ilze (Documenta Praehistorica, 2005)
Miniature Neolithic figurines in clay are a special topic of research. This especially concerns areas where their representation has so far been poor. While carrying out archaeological excavations in Northern Kurzeme, the north west coastal dune yone of Riga Bay, a ritual-like complex was recovered at Gipka A site belonging to the local Culture of Pit Ceramics. It consists of several large and smaller fireplaces and pits, with the finds of fragmentary clay figurines recovered under the palisade that surrounded the settlement. The head and body of the miniature anthropomorphic figurines in clay have original modelling. It is possible to single out two types of figurine: with rather broad cheekbones, and oval modelling of face. The large amount of ochre found in the settlement and the purposeful breaking of figurines are evidence of their role during a rite. Clay figurines have a symbolic meaning, and the signs depicted on them, incised walking stick-shape and other motifs, are the symbols of early farmers.
Keywords: Latvija; arheološke najdbe; neolitik; kipci; ceramic; keramika; simboli; symbol